Methods for the analysis of rhythmic and metrical responses to music in free movement trajectories - Naveda, Luiz (2015)
The process of retrieving meaningful information from rhythmic responses to music imposes several methodological challenges. For one side, the indivisible connection between body actions and the musical action confines the musical phenomenon in a closed cycle of action and perception. For another side, attempts to examine internalized rhythm descriptions always require body movements, which are the natural medium for musical actions. In this study, we propose strategies that are capable of retrieving emergent rhythmic and metrical structures encoded in free movements, which are less constrained by experimental designs and less dependent on previous assumptions. The first technique processes zero-crossing events across velocity patterns in order to estimate the changes of directions across metric levels. The second technique uses local accumulation of instantaneous velocity in order to describe the profiles of metric engagement abstracted from the morphology of the movement trajectories. The techniques help to trace comparisons and build representations of metrical structures. The paper discusses the possibilities and new perspectives of the methods by looking at two case studies with different analyses of movement responses to Argentinian chacarera and Afro-Brazilian samba music.